Photocatalytic Decomposition of Amoxicillin Using Zinc Ferrite Nanoparticles - Jezzini, Aya; Chen, Yujin; Davidson, Anne; Wallez, Gilles; Hamieh, Tayssir; Toufaily, Joumana (Crystals (Basel), 2024)
Catalysts enriched in Zinc ferrite (ZFO) were synthesized using coprecipitation and hydrothermal methods. Mixtures of crystalline nanoparticles (ZFO and α-Fe2O3, several allotropic varieties of FeO) were characterized by various techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM, SEM), N2 sorption, UV-visible spectrophotometry (UV-Vis) and X-ray photoelectron spectroscopy (XPS). After detailed characterizations, the catalytic performance of the solids (1 g/L) in the degradation of amoxicillin (AMX) (10 mg/L) as an antibiotic pollutant in water was evaluated. In addition, we used air as the oxygen source and adjusted the pH to 5.0. Consequently, the catalysts obtained via the hydrothermal method HT-ZFO had a high activity (100% of AMX removal in less than 100 min when an LED (75 W) light was used) compared to a similar mixture of oxides with graphene HT-ZFO-GO (a longer time of 150 min) that was necessary for the complete degradation of AMX. Impregnation with an aqueous solution containing 80 mg of GO obtained using Hummer’s method, reduced into RGO by an ultrasound treatment, enhances the initial reaction rate but is associated with a prolonged time for complete AMX removal (10 ppm in water) that we attribute to its spontaneous corrosion.